Ginger supplementation in quail as a nutritional alternative in egg production and quality - Oscar Patricio Núñez-Torres; Verónica Elizabeth Delgado-Álvarez; Roberto Ismael Almeida-Secará; Sandra Margarita Cruz Quintana (Journal of the Selva Andina Animal Science)
In this study, the behavior of ginger flour (Zingiber officinale) was evaluated on the productive parameters during the first stage of laying in quail (Coturnix coturnix japonica), it was carried out in five phases distributed in weeks (phase one, 1 and 2, phase two, 3 and 4, phase three, 5 and 6, phase four 7 and 8 and phase five 9 and 10) of posture. The variables to be studied were: feed consumption (g) feed conversion, mortality, (%), percentage of laying (%), egg quality expressed in (egg weight (g) shell thickness (mm), resistance of shell (kgf), yolk coloration. A completely randomized design with four treatments and six repetitions was used, as well as an analysis of variance and Tukey's test at 5%. The treatments used were: T1, T2 and T3 T0 (control), were applied in doses of ginger flour of: 0%, 0.2%, 0.4% and 0.6% respectively. The statistical differences between T3 and the control group, determined that the flour favors the consumption of food, especially in the final phases of the study, (T1, T2 and T3) compared to the control group. Feed conversion shows significant differences with T2 in the intermediate production phases compared to the control. The percentage of laying does not present significant differences, in addition to the quality of the eggs improved notabl e mind. Regarding mortality, there were significant differences especially in T3 compared to the control since the birds showed resistance to diseases. In relation to profitability, the results of T3 were superior, with a CRB of 1.19. Concluding that the inclusion of ginger flour improves the productive parameters and the quality of the eggs.